Pemanfaatan Video Animasi Interaktif untuk Meningkatkan Kemampuan Bahasa Inggris Mahasiswa PIAUD Kampus Diniah Putri Pekanbaru - ahmad, arimuliani; Rezki; Yulianto; Etfita, Fauzul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This Community Service activity aims to improve the English language skills of PIAUD students at the Diniah Putri Pekanbaru Campus through the use of interactive animated videos. This program is motivated by students' low ability to communicate in English and learning methods still dominated by conventional lectures. In its implementation, this activity includes the development of interactive animation-based materials, training for lecturers, and implementation in the classroom learning process. The evaluation results show that the use of interactive animated videos can significantly increase students' learning motivation, speaking skills, and understanding of the material. Participants also responded positively to the material's clarity and attractiveness. With this technology-based approach, it is hoped that students will have a more interesting and effective learning experience, supporting the formation of an innovative and interactive learning environment.